Gender and policing in the UK: historical perspectives on 50 years of equality legislation - Jackson, Louise A. (Policing and society, 2025)
This article demonstrates how historical and longitudinal inquiry – including a deep dive into archival sources – can add to our understanding of the processes of change and how they happen within the policing organisation. Using frameworks adapted from Feminist Institutionalism, it identifies variations in the type and pace of change across time, shows that trajectories were uneven and not one way, and explains how historical actors have operated within (and interacted with) institutional and contextual parameters in gendered ways and with gendering effects. Focusing on the debates surrounding the introduction, implementation and mobilisation of the 1975 Sex Discrimination Act (and equivalent legislation for Northern Ireland), it analyses the strategies and tools used by exogenous actors, relationships with internal actors, and capacity to produce internal change. Concentrating on the 1970s–1990s, it sets this within the broader trajectory of women’s appointment as police officers from 1915, the layering in of the separate structure of Policewomen’s Departments, and the work of senior female officers and members of the inspectorate in effecting slow, gradualist and pragmatic expansion of numbers and remit prior to the 1970s.